Vers une institutionnalisation de l’agriculture bio ? Étude de deux manifestations promotionnelles en Alsace - Denise Van Dam; Jean Nizet; Michel Streith (VertigO, 2017)
We consider organic farming as a « new social economic movement ». As such, it is crossed by several tensions pushing the movement to evolve. We make the hypothesis that an evolution is going on towards institutionnalization. We test this hypothesis by comparing two promotional events in Alsace : the Foire Eco-Bio d’Alsace, created in 1982 in a hostile environment to organic farming, and the Salon BiObernai, established in a more organic-favorable environment. We analyze this evolution through the prism of network contruction, as theorized by the sociology of networks of Callon and Latour. The hypothesis of institutionalization is partially confirmed. Through our research, a second hyothesis emerge, which refers to the theory of the generations. Indeed, the comparison between the two promotional events shows that the institutionnalization goes through a replacement of the generation that was in favour of radical organic farming by a generation that emphasizes the more consensual organic farming.